Extending design space of continuous inverse class‐FJ mode PAs. Issue 21 (1st October 2016) - Gao, Yong; Li, En; Guo, Gaofeng
Abstract : The impedance space of inverse class‐FJ mode power amplifiers (PAs) is extended by introducing a resistive part into the voltage waveform. Unlike traditional inverse class‐FJ mode, the new continuous inverse class‐FJ possesses a complex fundamental and third‐harmonic terminals. For validating the theory, a broadband PA working across 1.6–2.7 GHz is designed. The experimental results show a drain efficiency of 69–84.9% in the whole working band. The measured output power of the fabricated PA is 40.1–42.5 dBm with a gain of 10.6–12.5 dB across 1.6–2.7 GHz.